IMPACTOF THE ‘SHUTTLE TIME –BADMINTON’PROGRAM ON STUDENTS’PHYSICAL FITNESS - R. Ivanova; D. Simeonova (Trakia Journal of Sciences, 2024)
BWF's "SHUTTLE TIME" badminton training program was approved for seventh-grade students. The PURPOSE of the study was to trace its effect on the development of students’ motor abilities: speed, endurance, upper limbs’ explosive power, and agility. The research covered fourteen boys and nine girls, aged 13-14, students from 119 Secondary School "Acad. Mikhail Arnaudov", Sofia city. The methodology was applied to the elective subject ‘Racket sports’ in the education program of ‘Physical education and sport’in two school terms—36 school classes. The data were traced using the system for assessing the students’ physical fitness in the Republic of Bulgaria at the beginning and end of the 2022/23 school year. The statistical methods used for data processing were Variation analysis and Student's paired-sample t-test. The following RESULTS were obtained:The boys’ endurance and agility indicators showed an increase with a significant effect size (Cohen d up to 0.8), and the upper and lower limbs’ explosive powerindicator and speed indicator had a large effect size (Cohen d over 0.8). In girls, a large effect size (Cohen d over 0.8) was achieved in indicators for endurance, agility, and upper limbs’ explosive power, and a significant effect size (Cohen d up to 0.8) was obtained in the indicators for speed and lower limbs’ explosive power. The results were statistically significant, with a guaranteed probability: P (t)≥95%. The applied program has a significant impact on agility and endurance and a lesser impact on the upper and lower limbs’ explosive power and speed.